2012
DOI: 10.1175/jcli-d-11-00389.1
|View full text |Cite
|
Sign up to set email alerts
|

Eclipse Ice Core Accumulation and Stable Isotope Variability as an Indicator of North Pacific Climate

Abstract: The high accumulation rate and negligible amount of melt at Eclipse Icefield (3017 m) in the Saint Elias Range of Yukon, Canada, allows for the preservation of a high-resolution isotopic and glaciochemical records valuable for reconstruction of climatic variables. Each of the three Eclipse ice cores have a well-constrained depth-age scale with dozens of reference horizons over the twentieth century that permits an exceptional level of confidence in the results of the current calibration exercise. Stacked time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 53 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…Following earlier works of Hoffmann (2003) and Vuille et al (2003) for the Andes, Brown et al (2006) identified strong imprints of monsoons, meridional migration of the ITCZ and ENSO in tropical precipitation isotopic composition, through processes affecting rainout intensity and convection height. Other ice cores in the central TP, Arctic, Antarctic, and subpolar regions were also interpreted to depict rapid changes in atmospheric circulation after the mid-1970s (Kang et al 2002;Kaspari et al 2007;Schneider et al 2012;Kelsey et al 2012).…”
Section: Comparison With Lmdziso Simulations and Large Scale Climate mentioning
confidence: 99%
“…Following earlier works of Hoffmann (2003) and Vuille et al (2003) for the Andes, Brown et al (2006) identified strong imprints of monsoons, meridional migration of the ITCZ and ENSO in tropical precipitation isotopic composition, through processes affecting rainout intensity and convection height. Other ice cores in the central TP, Arctic, Antarctic, and subpolar regions were also interpreted to depict rapid changes in atmospheric circulation after the mid-1970s (Kang et al 2002;Kaspari et al 2007;Schneider et al 2012;Kelsey et al 2012).…”
Section: Comparison With Lmdziso Simulations and Large Scale Climate mentioning
confidence: 99%
“…In contrast to those from the NWC and PRC cores, snow accumulation records developed from cores drilled on the Eclipse Icefield in 1996 and 2002 (Wake et al, 2002;Kelsey et al, 2012) are highly and significantly correlated over their period of overlap (│R│ = 0.50; AD 1895 -1994), implying a much higher signal-to-noise ratio than in the Mt. Logan plateau records .…”
Section: The Eclipse Icefield Accumulation Recordmentioning
confidence: 70%
“…Years with anomalously high (low) accumulation in the PRC record, which were identified using the same criteria as Moore et al (2002a) and Rupper et al (2004), differ from the anomalous years identified by those authors for their composite meteorological field analyses, and (Holdsworth et al, 1992;Moore et al, 2002b); (b) the Mt. Logan PRC core ; and (c) the Eclipse Icefield cores (Kelsey et al, 2012) these differences cannot be accounted for solely by dating discrepancies.…”
Section: The Mt Logan Prc Accumulation Recordmentioning
confidence: 91%
See 2 more Smart Citations